A treasury of giant and monster stories - "Olliver, Jane" (Kingfisher London, 1992)
A collection of stories about giants, dragons and monsters, including classic tales by writers such as Oscar Wilde and E. Nesbit, as well as contributions from contemporary children's writers such as Virginia Haviland and Margaret Mahy.